(untitled) (Journal of the College of Basic Education, 2025)
The Current research aims to identify the family and its role in confronting the problem of test anxiety among children on a sample of sixth – grade middle school students. ( final stage exams). The research is considered a descriptive research, as the research relied on the Social survey method by sampling (purposive sampling ).It also adopted the questionnaire method by distributing the questionnaire to the research sample consisting of (50( male and female students to collect data in two private Lessons institutes ( AL Qimma and Tabarak Educational institute ) in the AL Mashtal erea-ALjedeada Baghdad . The researcher found that the level of students opinion regarding the mother s treatment of her childrens examination anxiety is very high among the research sample , this is according to the overall a verage relative importance index of (77,25)according to the approved standard (AKadiri,2011),IT was also shown that the level of students opinion regarding Following up on the mother and motivating her to confront her childrens exam anxiety is very high among the research sample this is according to the overall average relative importance index of (82).IT was also shown that the level of students opinion regading following up on the father and motivating his to confront his childrens exam anxiety is very high among the research sample , this is according the overall average relative importance index of (77,5) .It was also shown that the level of anxiety that children experience during revision and exam times is very high among the research sample , this is according the overall average relative importance index of (82).also there are significant differences in the anxiety that children experience during review and exam times ,according to the gender variable in favor of (females)on average of (74,55)and a standarad deviation of (8,50) . The research consists of three chapters ,the first consists of two section , rhe first sections , in which the research focused on the methodological framework of the research ,While the Second section defines the concepts and terminology .AS for the second chapter , the research dealt with the family and its role in following up and treating children in the sixth grode of middle School in the first section While the second section the research dealt with family and its role in following up on its children and improving their level of academic achievement . While the third section was exam anxiety and the role of family in facing its problems .While the third chapter dealt with field study where the field study procedures were laid out in the first section , the study data is presented and analyzed in the second section .The researcher developed (5)hypotheses and they were answered through the answers,then recommendation and sources